Input-output approach to cost-benefit-analysis of energy conservation methods - Henry, E.W. (Economic & Social Studies, 1977)
In this paper is proposed a method of using Input-Output (I-O) techniques for cost-benefit (G-B) analysis, in order to compare one method of conserving energy with another. Only energy conservation will be considered, although the methodology is applicable to many other kinds of problem. The outline of the paper is as follows: in the second part we discuss the 1974 1-0 data to be used as base for the C-B experiments. The third shows how these 1-0 data are applied as C-B tools to three energy conservation schemes for which numerical information was available. In the fourth part we standardise and compare results found in the third; whilst the fifth sets out some conclusions. An Appendix examines the common ground between traditional C-B formulae and traditional I-O analysis. Four useful aspects of the paper are the following; firstly, a version of a 1974 I-O transactions table is made available for general use, as well as multipliers for that version. Secondly, some insight is given on the substitution effects of the oil crisis; we compare the 1973 and 1974 household expenditure patterns and surmise that some differences are due to higher oil and energy prices. Thirdly, the paper attempts to integrate C-B analysis with I-O techniques and thus calculate secondary effects of investment schemes: Fourthly, the tools available through the above aspects are applied to three C-B problems, all relating to methods of saving energy, considered as investments.
Keywords: Input-output techniques; Energy conservation